Pengaruh Metode Cooperative Scrift dan Peran Orang Tua Terhadap Prestasi Belajar Bahasa Indonesia - Sigit Widiyarto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
AbstractLearning methods in the schools can determine the success students. But Masterylearning method is still less optimal. One of method to increase student activity iscooperatif scrift. This research used experimental method. The research findings:There is the effect of the method cooperatif scrift to achievement learn Indonesian. Byusing scrift Coopertif method can improve student achievement, so that better andproper administration of these methods will increase student learning outcomes. Thereis the influence of the role of parents to the student achievement Indonesian. The roleof parents can improve student achievement. The role of parents is very important tosupport the child in improving learning achievement in school. There is the influenceof cooperatif scrift methods and the role of parents simultaneously to achievementlearn Indonesian. Provision of appropriate methods target will create an optimallearning process. The role of parents both at home and at school can support betterresult.Keywords: cooperative scrift method, Role of Parents and The result of BahasaLearning